Dangerous in diamonds [large type] - Hunter, Madeline (Hunter, Madeline. Rarest blooms series., 2011)
Outrageously wealthy, the Duke of Castleford has little incentive to curb his profligate ways. When a bequest adds a small property to his vast holdings that houses The Rarest Blooms, a small flower business, it's of little interest to him ... until he lays eyes on its owner. Daphne Joyes is coolly mysterious, exquisitely beautiful, and utterly scathing toward a man of Castleford's stamp - in short, worthy of his most calculated seduction. (Bestseller)